Voltammetric studies of the redox mediator, cobalt phthalocyanine, with regard to its claimed electrocatalytic properties - Kozub, B; Compton, R (2010)
It is widely reported in the literature that cobalt phthalocyanine (CoPC) facilitates a wide variety of redox processes. This conclusion is often made without any comparison of analytical parameters (such as sensitivity and detection limit) for the reaction at both CoPC modified and a bare unmodified electrodes. Another important issue is a lack of full and proper study of the electrochemical properties of dissolved and adsorbed CoPC before adding an analyte to the solution. It is also generally reported, without presenting convincing argument, that the nature of active form of CoPC at the surface of carbon electrodes is always a monolayer. We report a thorough electrochemical study on the solution phase and solid phase cobalt phthalocyanine with regard to its claimed electrocatalytic properties towards oxidation of nitrite. The cyclic voltammetry of cobalt phthalocyanine has been examined in dimethyl sulfoxide (DMSO) and tetrahydrofuran (THF) at a glassy carbon (GC) electrode. In both solvents three redox couples are present: one ring based and two cobalt based processes. The aqueous voltammetry of CoPC adsorbed on basal plane pyrolytic graphite (BPPG) and edge plane pyrolytic graphite (EPPG) was also studied in phosphate buffer solution. Two couples are present: Co(II/I) and Co(III/II). Cyclic voltammetry experiments suggest that the number of electroactive adsorbed CoPC molecules on EPPG is approximately 3.5 times higher than on BPPG. The surface properties of both electrodes modified by immersing in 0.1 mM CoPC in dimethylformamide (DMF) solution were characterized by SEM and energy dispersive X-ray spectroscopy (EDS). It was observed that CoPC adsorbed on EPPG and BPPG electrodes exists as microcrystals, not as a monolayer reported in the literature for other carbon electrodes. The use of EPPG-CoPC modified electrode for sensing nitrite (NO2-) was also investigated. It was found that CoPC on EPPG has no influence on the oxidation of nitrite. © 2010 Elsevier B.V. All rights reserved.